39 Clues Book 11 : Vespers Rising - Korman, Gordon (New York : Scholastic Inc., 2011)
Fourteen-year-old Amy Cahill and her younger brother Dan thought they could return to their regular lives when they found the 39 clues. But the Vespers, powerful enemies, will stop at nothing to get the clues. And with the Vespers rising, the world is in jeopardy.
Keywords: Brothers and sisters -- Juvenile fiction; Orphans -- Juvenile fiction; Family secrets -- Juvenile fiction; Adventure stories; Brothers and sisters -- Fiction; Orphans -- Fiction; Secrets -- Fiction; Adventure and adventurers -- Fiction